IMPLEMENTASI PERDA NOMOR 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KOTA SEMARANG - Vina Dian Pratiwi; Yuwanto .; Turtiantoro . (Journal of Politic and Government Studies, 2015)
AbstractThe growing number of street vendors in downtown areas is incontrollable. Aprogram to comprehensively arrange and guide those street vendors is seriouslyneeded. The existence of street vendors in downtown is one of the factors that leadsto the problems such as traffic problem, crime rate, and waste problem. The growingnumber of street vendors has rushed the local government to make known the LocalRegulation Number 11 Year 2000 about The Street Vendor Arrangement andGuidance. Based on the local regulation, the government is expected to control themushrooming street vendors.Qualitative method was used in the research. During the research, descriptiveanalysis which is the method to provide systematic, factual, and accurate illustrationor description on the data was used. Primary data was obtained from interview andthe secondary data was obtained from document, archive, and direct observation toget the real condition of the case. The direct observation was done by involving inthe programs of Department of Marketplace like doing the patrol, meeting andrelocation. The data was then analyzed qualitatively in the forms of essay,illustration, and conclusion making of the observed signs.Semarang is a big city which has accommodated its street vendors based ontheLocal Regulation Number 11 Year 2000 about The Street Vendor Arrangementand Guidance. The regulation sets the place of business, permit, levies, rights, obligations and prohibitions, guidance, and penal provisions related to arrangementand guidance. The street vendors in all 16 districts in Semarang have increased to481 vendors in year 2012-2015. Ironically, illegal vendors which were only 3.884vendors in 2012 have increased to 4.856 in 2015. The obstacle in eradicating theregulation is that the weak supervision from the stakeholders, inconveniently locatedrelocation site, unavailability of transportation facilities, lack of legal awareness, andthe economic factors of the vendor like the inability to pay the levy, and from thestakeholders’ point of view which provides less guidance and comprehensiveinformation to the street vendor that results in the vendors who has limitedunderstanding of the dos and don’ts in trading.The recommendations to enhance the ability in doing the responsibilities, thestakeholders should be professional, highly-committed, honest, responsible, anddemocratic so incompetent stakeholders are not found during the implementation oflocal regulation. The guidance, supervision, and quality controlling by socializingand doing the patrol should be enhanced.Key words: Policy implementation. The implementation of local regulationnumber 11 year 2000 about The Street Vendor Arrangement and Guidance